Scientific Performance Analysis of the SYZ Telescope Design versus the RC Telescope Design *D. Ma & Z. Cai contributed equally to this paper. (21st December 2017) - Ma, Donglin; Cai, Zheng
Abstract: Recently, Su et al. propose an innovative design, referred as the "SYZ" design, for China's new project of a 12 m optical-infrared telescope. The SYZ telescope design consists of three aspheric mirrors with non-zero power, including a relay mirror below the primary mirror. SYZ design yields a good imaging quality and has a relatively flat field curvature at Nasmyth focus. To evaluate the science-compatibility of this three-mirror telescope, in this paper, we thoroughly compare the performance of SYZ design with that of Ritchey–Chrétien (RC) design, a conventional two-mirror telescope design. Further, we propose the Observing Information Throughput (OIT) as a metric for quantitatively evaluating the telescopes' science performance. We find that although a SYZ telescope yields a superb imaging quality over a large field of view, a two-mirror (RC) telescope design holds a higher overall throughput, a better diffraction-limited imaging quality in the central field of view (FOV < 5′) which is better for the performance of extreme Adaptive Optics (AO), and a generally better scientific performance with a higher OIT value.